Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Violet Swaggerty Goins, Church historian Becky Eaves, Ethel Swaggerty Wooden and Albert Watkins on Pauline's front porch; Cleveland, TN East Brainard Concord Baptist Cemetery